(3cJGH aj GdJhMjOs - (3eLghds ((3Ndjd GdRGhjs)
(3ChdgG (B:s
(3HYO GdHSedI ; QH GcTa dfG CSQGQ GdJfRjd hGQRbfG JdGhJg BfGA Gddjd hGdfgGQ HGdJQJjd GdMeO ddg GdPj CXgQ SdWGfg hLdGd s
(3BNQgG (B:s
(3hEf cGfJ eKd YOO GdOQ dG Edg EdG Gddg GdMcje GdcQje dG Edg EdG Gddg GdYdj GdYdXje SHMGf Gddg QH GdSehGGJ hQH GdYQT GdYXje GdMeO ddg QH GdYGdejfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds